Measurement of Carbon Emission Transfer in China's Construction Industry and Analysis of Spatial and Temporal Distribution of Carbon Emissions - Wenwen Xiao; Wenhao Song; Xuemei Pei; Lili Wang (Global Challenges)
Abstract The construction industry is an important material production sector in China's national economy, and the trade of goods and services between regions may lead to the transfer of carbon emissions from the construction industry. This study constructs a multiregion input–output table model containing 27 industries in 30 provinces in China from 2007 to 2017. It measures and analyzes carbon emissions and carbon transfer in China's construction industry, constructs a carbon emission transfer network for China's construction industry by combining a complex network model, and analyzes the spatial and temporal transfer structural characteristics of its network indicators. The results show that most provinces with higher carbon emissions from the construction industry are concentrated in the eastern coastal areas and regional center provinces, and in addition to the frequent carbon transfers within economically developed regions, the resource‐intensive provinces also frequently have carbon transfers with economically developed provinces. Based on the results of this study, a differentiated carbon emission reduction plan is formulated, and policy recommendations for optimizing carbon emission reduction in the construction industry in each region are proposed.